The status and role of genetic diversity of trees for the conservation and management of riparian ecosystems: A European experts' perspective. Issue 10 (20th July 2022) - Alimpić, Filip; Milovanović, Jelena; Pielech, Remigiusz; Hinkov, Georgi; Jansson, Roland; Dufour, Simon; Beza, Marcin; Bilir, Nebi; del Blanco, Luis Santos; Božič, Gregor; Bruno, Daniel; Chiarabaglio, Pier Mario; et al.
Abstract: Riparian vegetation supports high biodiversity providing many services and is, therefore, an important landscape element. Riparian ecosystems are subject to numerous pressures leading to population decline and genetic erosion of riparian plants. This may have cascading effects at various ecosystem levels, including decreasing ecosystem services, so identifying the current status of genetic diversity of riparian tree species is vital to improve the effectiveness of restoration efforts. We aimed to elicit expert views on the status and importance of genetic diversity of tree species, and conservation needs across European riparian ecosystems. Sharing of such information among researchers, managers and policymakers has the potential to enhance ecological restoration and management of riparian ecosystems. We identified experts in riparian genetic resources conservation and management across Europe. These included stakeholders with different perspectives, ranging from researchers to practitioners. We designed a set of questionnaires where our identified experts were asked to answer questions related to the status and conservation of genetic diversity of riparian tree species in their respective countries. Specifically, we asked about societal awareness, legislative tools, good practices and conservation or restoration projects accounting for intraspecific genetic diversity and differentiation of tree species in riparian ecosystems. Questionnaire responses were analysed and discussed in light of the scientific literature to define needs and priorities related to the management and conservation of genetic diversity of riparian tree species. The experts recognized that a combination of in situ and ex situ measures and/or integrative conservation of riparian ecosystems is the most appropriate option for conserving the genetic diversity of riparian tree species. Simultaneous application of conservation measures at the level of priority species, identified by experts, and protection of riparian areas are required. Synthesis and applications. This study revealed the importance of recognizing the ecological processes that shape the genetic diversity of riparian tree species in hydrographic networks (dendritic spatial configuration, specific patterns of gene flow among riparian populations, fragmentation of river by dams) but also the need to overcome socio‐economic barriers, such as lack of policy priority, deficiency in funding and weak legislation framework. Abstract : This study revealed the importance of recognizing the ecological processes that shape the genetic diversity of riparian tree species in hydrographic networks (dendritic spatial configuration, specific patterns of gene flow among riparian populations, fragmentation of river by dams) but also the need to overcome socio‐economic barriers, such as lack of policy priority, deficiency in funding and weak legislation framework.